Enhanced transverse electric phonon polaritons in two-hexagonal boron nitride-layer structures. (9th July 2018) - Cheng, Min; Fu, Ping; Chen, Shengyu; Tang, Xiaoteng; Chen, Xiyao; Lin, Yingting; Feng, Shangyuan
Abstract: The amplification and propagation properties of transverse electric (TE) phonon polaritons in a two-hexagonal boron nitride (hBN)-layer structure are investigated theoretically. The excitation of TE phonon polaritons with strong confinement in the two-hBN-layer structure is investigated numerically. We found that in the two-hBN-layer structure, a nearly perfect absorption exists, which originates from the excitation of the TE phonon polaritons with high effective index. When the incident angle is near the absorption angle, we found that a large photonic spin Hall effect of the reflected beam exists owing to the sharp decrease in Fresnel reflective coefficients around the perfect absorption.